Polyanion sodium ion battery positive electrode material, preparation method thereof and sodium ion battery
By using an inorganic carbon source with a specific specific surface area and doping sodium and transition metal positions in the positive electrode material of polyanionic sodium ion battery, the problem of unsatisfactory capacity, compaction and conductivity of the positive electrode material is solved, and the effect of performance improvement and production simplification is achieved.
Patent Information
- Application Number
- CN202510186245.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The capacity, compaction and conductivity performance of the existing polyanionic sodium ion battery cathode materials is not ideal, especially the problems of sodium-iron-based pyrophosphate materials are even more serious.
By selecting an inorganic carbon source with a specific specific surface area as the raw material for the carbon clad layer, and coordinating the sodium doping and transition metal doping scheme, the specific surface area and pore volume distribution of the positive electrode material are optimized, and the reaction site and phase purity are improved.
It effectively improves the capacity, compaction and conductivity of the positive electrode material, improves the compaction density of the positive electrode sheet, simplifies the production process, improves production safety, and is expected to be applied to large-scale production.
Smart Images

Figure CN119674061A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries and relates to a polyanion sodium ion battery positive electrode material and a preparation method thereof and a sodium ion battery. Background Art
[0002] Sodium-ion batteries have similar working principles to lithium-ion batteries and can still use existing lithium-ion production equipment without the need for additional equipment investment. These advantages have led to the rapid development of sodium-ion batteries.
[0003] The technical route of sodium-ion batteries is divided into Prussian blue compounds, transition metal oxides and polyanion compounds according to the type of positive electrode materials. Among them, Prussian blue compounds have a relatively open skeleton, and the discharge capacity and working voltage are relatively moderate; transition metal oxides have a small molecular weight, a large amount of sodium ion deintercalation, and a high discharge specific capacity; polyanion compounds have a stable three-dimensional skeleton, a high working voltage, high-rate charge and discharge characteristics and high stability. These three types of materials also face their own problems that need to be overcome: the crystal water in Prussian blue is difficult to remove, and the number of cycles is difficult to increase; transition metal oxides have a complex phase change process in the process of sodium deintercalation / intercalation, and the irreversible phase change will cause the collapse of its structure and the rapid attenuation of capacity, resulting in poor cycle life; common polyanion positive electrode materials are of various types and have different properties, mainly including phosphates, pyrophosphates, sulfates and mixed polyanions.
[0004] Among them, polyanion cathode materials have attracted widespread attention due to their stable crystal structure and low cost. Compared with layered oxide cathode materials, polyanion cathodes have abundant and low-priced raw materials, such as iron, which makes iron-based polyanion compounds have great advantages in the competition for large-scale production, economical and environmentally friendly sodium ion battery cathode materials. There are three-dimensional sodium ion diffusion channels in polyanion cathode materials, which have excellent electrode kinetics, but the performance of the material, such as capacity, compaction and conductivity, is not very ideal, especially for sodium iron-based pyrophosphate materials, where the above problems are more serious.
[0005] Based on the above problems, the current solutions include improving the compaction of the material's electrode by mixing large and small particles. However, this method has high requirements for the precursor and requires the preparation of precursors of different particle sizes. Secondly, the material usually controls the production of impurities in the positive electrode material by controlling the ratio of sodium and transition metal elements, but this process requires precise control of the ratio of sodium to transition metals, and it is impossible to control whether the reaction occurs fully, resulting in low material purity and affecting the material's electrical properties such as capacity.
[0006] Therefore, how to improve the capacity, compaction and conductivity of polyanion positive electrode materials in sodium-ion batteries and improve the compaction density of positive electrode sheets is a technical problem that needs to be solved urgently. Summary of the invention
[0007] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a polyanion sodium ion battery positive electrode material and a preparation method thereof and a sodium ion battery. The positive electrode material provided by the present invention can effectively improve the capacity, compaction and conductivity of the positive electrode material by selecting an inorganic carbon source with a specific specific surface area as the raw material of the carbon coating layer, and coordinating the sodium doping and transition metal doping schemes; and also improve the compaction density of the positive electrode sheet obtained from the above positive electrode material.
[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0009] In a first aspect, the present invention provides a polyanion sodium ion battery positive electrode material, the polyanion sodium ion battery positive electrode material comprising a polyanion positive electrode matrix material and a carbon coating layer coated on the surface of the polyanion positive electrode matrix material;
[0010] The polyanion positive electrode matrix material is also doped with sodium and transition metal;
[0011] The carbon source of the carbon coating layer includes an inorganic carbon source, and the specific surface area of the inorganic carbon source is 150-300m 2 / g.
[0012] The specific surface area of the inorganic carbon source can be 150 m 2 / g, 160m 2 / g, 170m 2 / g, 180m 2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, 240m 2 / g, 250m 2 / g, 260m 2 / g, 270m 2 / g, 280m 2 / g, 290m 2 / g or 300m 2 / g, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0013] The polyanion sodium ion battery positive electrode material provided by the present invention is a specific 150-300m 2 / g range as a raw material to coat the base material with a carbon coating layer, which is beneficial to the rapid deintercalation of sodium ions and the improvement of the ionic and electronic conductivity of the material; the sodium doping and transition metal doping in the positive electrode base material work together to optimize the specific surface area and pore volume distribution of the positive electrode material, increase the reaction sites of the positive electrode material, optimize the phase purity of the positive electrode material, improve the utilization rate of the positive electrode material, and thus increase the capacity of the positive electrode material; thereby effectively improving the capacity, compaction and conductivity of the positive electrode material; at the same time, since the conductive agent carbon material has been fully integrated with the positive electrode material, the use of conductive agents with low compaction density can be reduced in the preparation process of the electrode sheet, thereby also improving the compaction density of the positive electrode sheet obtained from the above-mentioned positive electrode material.
[0014] In the present invention, the inorganic carbon source, the specific surface area of the inorganic carbon source and the sodium doping and transition metal doping in the positive electrode matrix material are indispensable and must work synergistically to jointly solve the problems of poor material conductivity, low capacity and low compaction.
[0015] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the technical objectives and beneficial effects of the present invention can be better achieved and realized.
[0016] Preferably, the chemical formula of the polyanion positive electrode matrix material is Na x L y Fe a M b (PO4)2P2O7, wherein 3.5≤x+y≤4, 0<y<0.1, 1.32<(x+y) / (a+b)<1.38, b>0, L is a sodium doping element, and M is a transition metal doping element.
[0017] For example, the x may be 3.41, 3.45, 3.5, 3.6, 3.7, 3.8 or 3.9, etc.; the y may be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.099, etc.; the a may be 2, 2.1, 2.2, 2.3, 2.4, 2.5, 2.6, 2.7, 2.8, 2. 85, 2.9, 2.91, 2.92, 2.93, 2.94, 2.95, 2.96, 2.97, 2.98 or 2.99, etc.; the b can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09 or 0.1, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0018] In the present invention, the polyanionic cathode matrix material is selected as an iron-based pyrophosphate phosphate material, and an inorganic carbon source with a specific surface area of 150 - 300 m 2 / g is more beneficial to improving the conductivity of the cathode material and improving the electrode sheet resistance; and by regulating Na x L y Fe a M b (PO4)2P2O7 such that 3.5 ≤ x + y ≤ 4, 0 < y < 0.1, 1.32 < (x + y) / (a + b) < 1.38, and b > 0, thereby better regulating the doping amounts at the sodium site and the transition metal site, and further enhancing the discharge specific capacity of the material.
[0019] Preferably, in the Na x L y Fe a M b (PO4)2P2O7, 0 < b ≤ 0.05, such as 0.005, 0.01, 0.015, 0.02, 0.025, 0.03, 0.035, 0.04, 0.045 or 0.05, etc., but not limited to the listed values, and other unlisted values within this numerical range are equally applicable.
[0020] In the present invention, further regulating the stoichiometric ratio of the doping element at the transition metal site in the polyanionic cathode matrix material to be 0 < b ≤ 0.05 can better enhance the discharge specific capacity of the material and control the generation of transition metal impurities.
[0021] Preferably, the weighted atomic radius of the M element is 49 - 95 pm, such as 49 pm, 50 pm, 55 pm, 30 pm, 65 pm, 70 pm, 75 pm, 80 pm, 85 pm, 90 pm or 95 pm, etc., but not limited to the listed values, and other unlisted values within this numerical range are equally applicable.
[0022] In the present invention, selecting the M element with a weighted atomic radius of 49 - 95 pm can further achieve element substitution for iron element without substituting the sodium site and causing hindrance to sodium ion transport; for example, the M element includes but is not limited to at least one of Zr, Al, Zn, Mg, Ti, Nb, Y, Mo or Mn, etc.
[0023] Preferably, the element L doped at the sodium site includes Li and / or K, etc.
[0024] Preferably, the ash content of the inorganic carbon source < 3%, such as 0.5%, 1%, 1.5%, 2%, 2.5%, 2.6%, 2.7%, 2.8% or 2.9%, etc., but not limited to the listed values, and other unlisted values within this numerical range are equally applicable.
[0025] In the present invention, the ash content of the inorganic carbon source is controlled to be less than 3%, thereby obtaining an inorganic carbon source with higher purity and better conductivity, which can better improve the powder conductivity of the positive electrode material.
[0026] Preferably, the powder conductivity of the inorganic carbon source is greater than 1×10 4 S / cm, for example 1.5×10 4 S / cm, 2×10 4 S / cm, 2.5×10 4 S / cm, 3×10 4 S / cm, 3.5×10 4 S / cm, 4×10 4 S / cm, 4.5×10 4 S / cm, 5×10 4 S / cm, 5.5×10 4 S / cm, 6×10 4 S / cm, 6.5×10 4 S / cm, 7×10 4 S / cm, 7.5×10 4 S / cm, 8×10 4 S / cm, 8.5×10 4 S / cm, 9×10 4 S / cm, 9.5×10 4 S / cm or 1×10 5 S / cm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0027] In the present invention, the powder conductivity is selected to be greater than 1×10 4 S / cm inorganic carbon source with high conductivity can form a good ion-electron transfer channel inside the polyanion positive electrode matrix material, improve the sodium ion transmission efficiency of the material body, and reduce the material resistance.
[0028] Preferably, the polyanion positive electrode matrix material in the present invention is also doped with a carbon material, and the carbon material is consistent with the raw material of the carbon coating layer.
[0029] Preferably, the specific surface area of the polyanion sodium ion battery positive electrode material is 8 to 20 m 2 / g, for example 8m 2 / g, 8.5m 2 / g, 9m 2 / g, 9.5m 2 / g, 10m 2 / g, 10.5m 2 / g, 11m 2 / g, 11.5m2 / g, 12m 2 / g, 12.5m 2 / g, 13m 2 / g, 13.5m 2 / g, 14m 2 / g, 14.5m 2 / g, 15m 2 / g, 15.5m 2 / g, 16m 2 / g, 16.5m 2 / g, 17m 2 / g, 17.5m 2 / g, 18m 2 / g, 18.5m 2 / g, 19m 2 / g, 19.5m 2 / g or 20m 2 / g, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the polyanion sodium ion battery positive electrode material has micropores, and the volume ratio of the micropores is 30% to 50%, for example, 30%, 33%, 35%, 38%, 40%, 43%, 45%, 48% or 50%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] In the present invention, the volume of micropores refers to the space occupied by micropores (pore diameter less than 2 nm) in the positive electrode material of the polyanion sodium ion battery.
[0032] The polyanion sodium ion battery positive electrode material provided by the present invention has a specific surface area adjusted to 8-20 m 2 / g and / or the volume ratio of micropores is 30%~50%, which further increases the contact area between the electrode and the electrolyte, thereby improving the discharge specific capacity of the material.
[0033] Preferably, after the polyanion sodium ion battery positive electrode material is compacted at a pressure of 3t, its compaction density is 1.8-2.2 g / cm 3 , for example 1.8 g / cm 3 , 1.85g / cm 3 , 1.9g / cm 3 , 1.95g / cm 3 , 2g / cm 3 , 2.05g / cm 3 , 2.1g / cm 3 , 2.15g / cm 3 or 2.2g / cm3 The electronic conductivity of the compacted powder is 3×10 -6 ~6×10 -6 S / cm, for example 3×10 -6 S / cm, 3.5×10 -6 S / cm, 4×10 -6 S / cm, 4.5×10 -6 S / cm, 5×10 -6 S / cm, 5.5×10 -6 S / cm or 6×10 - 6 S / cm, etc., but are not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0034] The polyanion sodium ion battery positive electrode material provided by the invention has high compaction density and excellent electrical conductivity.
[0035] Preferably, the phase purity of the polyanion sodium ion battery positive electrode material is greater than 90%, for example 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99% or 99.9%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0036] It should be noted that the phase purity in the present invention refers to the peak area of all polyanion sodium ion battery positive electrode materials / all peak areas in the XRD spectrum obtained after subjecting the polyanion sodium ion battery positive electrode material to an X-ray diffraction test (XRD test).
[0037] In addition, the specific test method and test parameters of the X-ray diffraction test (XRD test) are also conventional technical solutions. Exemplarily, the present invention provides a specific test process for performing XRD test on the positive electrode material of a polyanion sodium ion battery: the sieved powder is evenly filled into the sample slot to ensure that the X-rays can accurately irradiate the sample, the scanning range is set to 10-90 degrees, the step is 0.02, and the diffraction signal is collected to obtain the XRD spectrum.
[0038] The phase purity of the polyanion sodium ion battery positive electrode material provided by the present invention is greater than 90%, and the phase purity is relatively high, thereby improving the utilization rate of the unit active material and further improving the discharge specific capacity of the positive electrode material.
[0039] In a second aspect, the present invention provides a method for preparing the polyanion sodium ion battery positive electrode material as described in the first aspect, the preparation method comprising the following steps:
[0040] Mixing a sodium source, a sodium doping source, a transition metal source, a transition metal doping source, an inorganic carbon source and a solvent to obtain a mixed solution, and spray-drying the mixed solution to obtain a precursor material;
[0041] Sintering the precursor material to obtain the polyanion sodium ion battery positive electrode material;
[0042] The specific surface area of the inorganic carbon source is 150-300 m 2 / g.
[0043] The specific surface area of the inorganic carbon source can be 150 m 2 / g, 160m 2 / g, 170m 2 / g, 180m 2 / g, 190m 2 / g, 200m 2 / g, 210m 2 / g, 220m 2 / g, 230m 2 / g, 240m 2 / g, 250m 2 / g, 260m 2 / g, 270m 2 / g, 280m 2 / g, 290m 2 / g or 300m 2 / g, etc., but are not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0044] The preparation method provided by the present invention adopts a spray drying process to prepare a polyanion sodium ion battery positive electrode material, which can effectively avoid the segregation phenomenon produced by the material during freeze drying or natural drying, improve the uniformity of the carbon coating layer, and obtain a polyanion sodium ion battery positive electrode material with high phase purity and moderate specific surface area and pore volume distribution; and is expected to be applied to large-scale production.
[0045] In the present invention, if the carbon source is an organic carbon source, such as glucose, sucrose, etc., even with the same specific surface area, good conductivity cannot be achieved. This is because the carbonization degree of the organic carbon source is not fixed as the calcination temperature or calcination time changes, so that the carbon content in the positive electrode material is uncertain, which in turn affects the performance and stability of the material.
[0046] Taking the total mass of the non-solvent components in the mixed solution as 100%, the amount of the inorganic carbon source added is 2% to 6%, for example, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5% or 6%, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0047] In the present invention, the amount of the inorganic carbon source added is preferably 2% to 6% of the total mass of the raw materials in the preparation process of the polyanion sodium ion battery positive electrode material, which can not only form a uniformly coated and conductive carbon coating layer on the surface of the polyanion positive electrode matrix material, but also allow the carbon material to be further doped into the polyanion positive electrode matrix material, thereby better improving the capacity and conductivity of the positive electrode material.
[0048] Preferably, the particle size of the sodium doping source is D50<200 nm, and D100<10 μm.
[0049] For example, the particle size D50 of the sodium-site doping source can be 50nm, 75nm, 100nm, 125nm, 150nm, 175nm or 190nm, etc.; the particle size D100 of the sodium-site doping source can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 9.9μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0050] Preferably, the particle size of the sodium-site doping source satisfies: 1.0<(D90-D10) / D50<3.0, for example, 1.1, 1.3, 1.5, 1.8, 2, 2.3, 2.5, 2.8 or 2.9, etc.
[0051] Preferably, the band gap width of the sodium-site doping source is 1~10eV, for example, 1eV, 2eV, 3eV, 4eV, 5eV, 6eV, 7eV, 8eV, 9eV or 10eV, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0052] Preferably, the particle size of the transition metal doping source is D50<200 nm, and D100<10 μm.
[0053] For example, the particle size D50 of the transition metal doping source can be 50nm, 75nm, 100nm, 125nm, 150nm, 175nm or 190nm, etc.; the particle size D100 of the transition metal doping source can be 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm or 9.9μm, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0054] Preferably, the particle size of the transition metal doping source satisfies: 1.0<(D90-D10) / D50<3.0, for example 1.1, 1.3, 1.5, 1.8, 2, 2.3, 2.5, 2.8 or 2.9, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0055] Preferably, the band gap width of the transition metal doping source is 1~10eV, for example, 1eV, 2eV, 3eV, 4eV, 5eV, 6eV, 7eV, 8eV, 9eV or 10eV, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0056] In the preparation process of the present invention, the particle size distribution and band gap distribution of the doping source (sodium-site doping source and / or transition metal-site doping source) are regulated to ensure good and uniform doping during the material generation process, so that the additive will not be unable to be doped into the bulk phase of the material to cause the generation of impurities, thereby better improving the phase purity of the obtained polyanion sodium ion battery positive electrode material; and the doping of additives with suitable band gaps will not increase the resistance of the material while improving the capacity performance of the positive electrode material.
[0057] Preferably, the sintering heating rate is 1-5°C / min, for example, 1°C / min, 2°C / min, 3°C / min, 4°C / min or 5°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0058] Preferably, the sintering holding temperature is 450-600°C, for example 450°C, 475°C, 500°C, 525°C, 550°C, 575°C or 600°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0059] Preferably, the sintering holding time is 8 to 16 hours, for example 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours or 16 hours, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0060] It should also be noted that the present invention does not impose any special restrictions on the selection of specific raw material types in the preparation process, and the present invention is applicable to all types of raw materials that can be used to prepare polyanion sodium ion battery positive electrode materials.
[0061] For example, the sodium source includes but is not limited to at least one of sodium carbonate, sodium phosphate or sodium nitrate.
[0062] For example, the iron source includes but is not limited to at least one of iron phosphate, iron nitrate or iron oxide.
[0063] For example, the phosphorus source includes but is not limited to at least one of sodium dihydrogen phosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, phosphoric acid or sodium hypophosphite.
[0064] For example, the inorganic carbon source includes but is not limited to at least one of carbon nanotubes, carbon nanofibers, conductive carbon black, or graphene.
[0065] Furthermore, the raw materials in the mixing process of the present invention may also include a reducing agent to avoid the change of the valence state of iron, such as citric acid or ascorbic acid.
[0066] In addition, the atmosphere during the sintering process of the present invention can be a protective atmosphere, such as a nitrogen atmosphere and / or an inert gas atmosphere, etc. The inert gas includes argon or helium, etc.
[0067] In a third aspect, the present invention provides a positive electrode plate, comprising a positive electrode collector and a positive electrode active material layer located on at least one side surface of the positive electrode collector; the positive electrode active material layer comprises a binder and the polyanion sodium ion battery positive electrode material described in the first aspect or the polyanion sodium ion battery positive electrode material prepared by the preparation method described in the second aspect.
[0068] Since the polyanion sodium ion battery positive electrode material provided by the present invention has excellent capacity, powder compaction density and electrical conductivity, when applied to the positive electrode plate, less or no conductive agent can be added, thereby improving the stripping force and compaction of the plate, thereby effectively reducing the resistance of the plate.
[0069] It can be understood that, except that no additional conductive agent is required for the positive electrode plate in the present invention, the rest of the structure, raw materials and preparation process are all conventional technical solutions, and those skilled in the art can make adaptive selections and adjustments based on actual needs.
[0070] For example, the preparation method of the positive electrode sheet in the present invention can adopt a wet slurry coating method or a dry film forming preparation method.
[0071] In the positive electrode active material layer, the mass ratio of the polyanion sodium ion battery positive electrode material and the binder is (85~92):(15~8), for example, 85:15, 86:14, 87:13, 88:12, 89:11, 90:10, 91:9 or 92:8, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0072] In a fourth aspect, the present invention further provides a sodium ion battery, comprising the polyanion sodium ion battery positive electrode material as described in the first aspect, or the polyanion sodium ion battery positive electrode material prepared by the preparation method as described in the second aspect, or the positive electrode sheet as described in the third aspect.
[0073] Compared with the prior art, the present invention has the following beneficial effects:
[0074] (1) The polyanion sodium ion battery positive electrode material provided by the present invention is a specific 150~300m 2 / g range as a raw material to coat the base material with a carbon coating layer, and cooperate with the sodium doping and transition metal doping in the positive electrode base material to work together to optimize the specific surface area and pore volume distribution of the positive electrode material, increase the reaction sites of the positive electrode material, optimize the phase purity of the positive electrode material, improve the utilization rate of the positive electrode material, and then increase the capacity of the positive electrode material; thereby effectively improving the capacity, compaction and conductivity of the positive electrode material; and also improving the compaction density of the positive electrode sheet obtained from the above positive electrode material.
[0075] (2) The preparation method provided by the present invention adopts a spray drying process to prepare a polyanion sodium ion battery positive electrode material, which can effectively avoid the segregation phenomenon of the material produced during freeze drying or natural drying, improve the uniformity of the carbon coating layer, and obtain a polyanion sodium ion battery positive electrode material with high phase purity and moderate specific surface area and pore volume distribution; simplify the production process, improve production safety, and is expected to be applied to large-scale production.
[0076] (3) Since the polyanion sodium ion battery positive electrode material provided by the present invention has excellent capacity, powder compaction density and electrical conductivity, when applied to the positive electrode plate, less or no conductive agent can be added, thereby improving the peeling force and compaction of the plate, thereby effectively reducing the resistance of the plate. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 This is a SEM image of the polyanion sodium ion battery positive electrode material provided in Example 1.
[0078] Figure 2 This is a charge and discharge curve diagram of the first week of the sodium ion battery provided in Example 1. DETAILED DESCRIPTION
[0079] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0080] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" and any variations thereof in this application are intended to cover non-exclusive inclusions.
[0081] In the description of this application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of this application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.
[0082] Example 1
[0083] This embodiment provides a polyanion sodium ion battery positive electrode material, the polyanion sodium ion battery positive electrode material comprising a polyanion positive electrode matrix material and a carbon coating layer coated on the surface of the polyanion positive electrode matrix material;
[0084] The chemical formula of the polyanion positive electrode matrix material is Na 3.95 K 0.05 Fe 2.95 Zr 0.05 (PO4)2P2O7, the Na 3.95 K 0.05 Fe 2.95 Zr 0.05 (PO4)2P2O7 is also doped with carbon nanotubes;
[0085] The carbon sources of the carbon coating layer and the doped carbon material are carbon nanotubes. The specific surface area, ash content and electrical conductivity of the carbon nanotubes are listed in Table 1.
[0086] The preparation method of the polyanion sodium ion battery positive electrode material is as follows:
[0087] (1) According to Na 3.95 K 0.05 Fe 2.95 Zr 0.05 Sodium phosphate, iron phosphate, sodium doping source potassium carbonate, citric acid and deionized water solvent are weighed and mixed in a stoichiometric ratio of (PO4)2P2O7 to obtain a first mixed solution; zirconium oxide, an inorganic carbon source, carbon nanotubes and deionized water are mixed to obtain a second mixed solution, and the amount of carbon nanotubes added is 4% of the total mass of all non-solvent raw materials; the first mixed solution and the second mixed solution are mixed to obtain a mixed solution; the mixed solution is ball-milled and then spray-dried to obtain a precursor material;
[0088] (2) heating the precursor material to 500° C. at a heating rate of 5° C. / min in a nitrogen atmosphere and then keeping the temperature for 12 hours to obtain the polyanion sodium ion battery positive electrode material;
[0089] Among them, the particle size and band gap of the sodium-doping source potassium carbonate and the transition metal-doping source zirconium oxide are shown in Table 1.
[0090] Figure 1 The SEM image of the polyanion sodium ion battery positive electrode material provided in Example 1 is shown. Figure 1 It can be seen that the primary particles of the material are nanoparticles with a large number of micropores on the surface, which provide a suitable surface area for the positive electrode material and provide good attachment sites for the positive electrode material reaction, thereby increasing the capacity of the positive electrode material.
[0091] Example 2
[0092] This embodiment provides a polyanion sodium ion battery positive electrode material, the polyanion sodium ion battery positive electrode material comprising a polyanion positive electrode matrix material and a carbon coating layer coated on the surface of the polyanion positive electrode matrix material;
[0093] The chemical formula of the polyanion positive electrode matrix material is Na 3.95 K 0.05 Fe 2.99 Zr 0.01 (PO4)2P2O7, the Na 3.95 K 0.05 Fe 2.99 Zr 0.01 (PO4)2P2O7 is also doped with carbon nanotubes;
[0094] The carbon sources of the carbon coating layer and the doped carbon material are carbon nanotubes. The specific surface area, ash content and electrical conductivity of the carbon nanotubes are shown in Table 1.
[0095] The preparation method of the polyanion sodium ion battery positive electrode material is as follows:
[0096] (1) According to Na 3.95 K 0.05 Fe 2.99 Zr 0.01 Sodium phosphate, iron phosphate, sodium doping source potassium carbonate, citric acid and deionized water solvent are weighed and mixed in a stoichiometric ratio of (PO4)2P2O7 to obtain a first mixed solution; zirconium oxide, an inorganic carbon source carbon nanotube and deionized water are mixed to obtain a second mixed solution, and the amount of carbon nanotube added is 2% of the total mass of all non-solvent raw materials; the first mixed solution and the second mixed solution are mixed to obtain a mixed solution; the mixed solution is ball-milled and then spray-dried to obtain a precursor material;
[0097] (2) heating the precursor material to 600° C. at a heating rate of 5° C. / min in a nitrogen atmosphere and then keeping the temperature for 8 hours to obtain the polyanion sodium ion battery positive electrode material;
[0098] Among them, the particle size and band gap of the sodium-doping source potassium carbonate and the transition metal-doping source zirconium oxide are shown in Table 1.
[0099] Example 3
[0100] This embodiment provides a polyanion sodium ion battery positive electrode material, the polyanion sodium ion battery positive electrode material comprising a polyanion positive electrode matrix material and a carbon coating layer coated on the surface of the polyanion positive electrode matrix material;
[0101] The chemical formula of the polyanion positive electrode matrix material is Na 3.95 K 0.05 Fe 2.97 Zn 0.03 (PO4)2P2O7, the Na 3.95 K 0.05 Fe 2.97 Zn 0.03 (PO4)2P2O7 is also doped with conductive carbon black;
[0102] The carbon source of the carbon coating layer and the doped carbon material is conductive carbon black. The specific surface area, ash content and conductivity of the conductive carbon black are shown in Table 1.
[0103] The preparation method of the polyanion sodium ion battery positive electrode material is as follows:
[0104] (1) According to Na 3.95 K 0.05 Fe 2.97 Zn 0.03 Sodium phosphate, iron phosphate, sodium doping source potassium carbonate, citric acid and deionized water solvent are weighed and mixed in a stoichiometric ratio of (PO4)2P2O7 to obtain a first mixed solution; transition metal doping source zinc oxide, inorganic carbon source conductive carbon black and deionized water are mixed to obtain a second mixed solution, and the amount of conductive carbon black tube added is 4% of the total mass of all non-solvent raw materials; the first mixed solution and the second mixed solution are mixed to obtain a mixed solution; the mixed solution is ball-milled and then spray-dried to obtain a precursor material;
[0105] (2) heating the precursor material to 450° C. at a heating rate of 5° C. / min in a nitrogen atmosphere and then keeping the temperature for 16 hours to obtain the polyanion sodium ion battery positive electrode material;
[0106] Among them, the particle size and band gap of the sodium-doping source potassium carbonate and the transition metal-doping source zinc oxide are shown in Table 1.
[0107] Example 4
[0108] The difference between this embodiment and embodiment 1 is that in this embodiment, the specific surface area of the carbon nanotubes is listed in Table 1.
[0109] The rest of the preparation methods and parameters were the same as those in Example 1.
[0110] Example 5
[0111] The difference between this embodiment and embodiment 1 is that in this embodiment, the specific surface area of the carbon nanotubes is listed in Table 1.
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Example 6
[0114] The difference between this embodiment and embodiment 1 is that in this embodiment, the chemical formula of the polyanion positive electrode matrix material is Na 3.95 K 0.05 Fe 2.9 Zr 0.1 (PO4)2P2O7.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Example 7
[0117] The difference between this embodiment and embodiment 1 is that in this embodiment, the ash content of the carbon nanotubes is listed in Table 1.
[0118] The rest of the preparation methods and parameters were the same as those in Example 1.
[0119] Example 8
[0120] The difference between this embodiment and embodiment 1 is that in this embodiment, the conductivity of the carbon nanotubes is listed in Table 1.
[0121] The rest of the preparation methods and parameters were the same as those in Example 1.
[0122] Example 9
[0123] The difference between this embodiment and embodiment 1 is that in this embodiment, the particle size of the sodium doping source potassium carbonate is as shown in Table 1.
[0124] The rest of the preparation methods and parameters were the same as those in Example 1.
[0125] Example 10
[0126] The difference between this embodiment and embodiment 1 is that in this embodiment, the sodium-site doping source is adjusted to potassium silicate, and the band gap of the sodium-site doping source is shown in Table 1.
[0127] The rest of the preparation methods and parameters were the same as those in Example 1.
[0128] Embodiment 11
[0129] The difference between this embodiment and embodiment 1 is that in this embodiment, the particle size of the transition metal doping source zirconium oxide is as shown in Table 1.
[0130] The rest of the preparation methods and parameters were the same as those in Example 1.
[0131] Example 12
[0132] The difference between this embodiment and embodiment 1 is that in this embodiment, the transition metal doping source is adjusted to zirconium silicate, and the band gap of the transition metal doping source zirconium silicate is shown in Table 1.
[0133] The rest of the preparation methods and parameters were the same as those in Example 1.
[0134] Comparative Example 1
[0135] The difference between this comparative example and Example 1 is that the specific surface area of the carbon nanotubes in this comparative example is listed in Table 1.
[0136] The rest of the preparation methods and parameters were the same as those in Example 1.
[0137] Comparative Example 2
[0138] The difference between this comparative example and Example 1 is that the specific surface area of the carbon nanotubes in this comparative example is listed in Table 1.
[0139] The rest of the preparation methods and parameters were the same as those in Example 1.
[0140] Comparative Example 3
[0141] The difference between this comparative example and Example 1 is that the carbon source in this comparative example is glucose, that is, the organic carbon source is replaced by an inorganic carbon source.
[0142] The rest of the preparation methods and parameters were the same as those in Example 1.
[0143] Comparative Example 4
[0144] The difference between this comparative example and Example 1 is that the chemical formula of the polyanion positive electrode matrix material in this comparative example is Na4Fe3(PO4)2P2O7, that is, no sodium site and transition metal iron site doping are performed.
[0145] In the preparation method, sodium carbonate and zirconium oxide are not added.
[0146] The rest of the preparation methods and parameters were the same as those in Example 1.
[0147] Table 1 shows the parameters of the carbon source, the sodium doping source and the transition metal doping source provided in Examples 1-12 and Comparative Examples 1-4, where the unit of specific surface area is m 2 / g, the unit of ash content is %, and the unit of conductivity is ×10 4S / cm, the unit of particle size D50 is nm, the unit of particle size D100 is μm, the unit of band gap is eV, and span is defined as (D90-D10) / D50.
[0148] Table 1
[0149]
[0150] The polyanion sodium ion battery positive electrode materials provided in Examples 1-12 and Comparative Examples 1-4 were tested for specific surface area, micropore volume ratio, powder compaction density under 3t pressure, powder electronic conductivity under 3t pressure and phase purity.
[0151] (a) Specific surface area and micropore volume ratio: both were tested using the nitrogen adsorption-desorption method.
[0152] (b) Powder compaction density under 3t pressure and powder electronic conductivity under 3t pressure: Under the condition of an applied pressure of 3t (tons), the compaction density meter and powder resistivity were tested respectively.
[0153] (c) Phase purity: Fill the sieved powder evenly and flatly into the sample slot to ensure that the X-rays can accurately irradiate the sample. Set the instrument scanning range to 10-90 degrees, step 0.02, collect the diffraction signal, and obtain the XRD spectrum. From the obtained XRD spectrum, calculate the ratio of the peak area of all polyanion sodium ion battery positive electrode materials to all peak areas, which is the phase purity.
[0154] The test results of the above tests are shown in Table 2.
[0155] Table 2
[0156]
[0157] The polyanion sodium ion battery positive electrode materials provided in Examples 1-12 and Comparative Examples 1-4 were used to prepare sodium ion batteries and the battery performance was tested.
[0158] I. Battery Preparation
[0159] Positive electrode sheet: The positive electrode material and PVDF (binder) are mixed in NMP at a mass ratio of 90:10, the mixed solution is coated on aluminum foil, and a positive electrode sheet with a diameter of 12 mm is obtained after drying, rolling and cutting.
[0160] Negative electrode: Use a sodium plate with a diameter of 14mm.
[0161] Diaphragm: Glass fiber diaphragm with a diameter of 16mm
[0162] Electrolyte: The solvent is EC (ethylene carbonate): DEC (diethyl carbonate) in a volume ratio of 3:7, and the solute is 1 mol / L sodium hexafluorophosphate.
[0163] Assembly: Assemble the battery in the order of negative electrode shell - spring - gasket - negative electrode sheet - diaphragm - electrolyte - positive electrode sheet - positive electrode shell.
[0164] II Performance Test
[0165] (a) Pole piece compaction density test: The pole piece is rolled using a roller machine, and the pole piece compaction density data is obtained by the pole piece surface density / (pole piece thickness-aluminum foil thickness).
[0166] (b) Test of electrode resistance: The four-probe method is used to test the electrode resistance. Four probes are placed at equal intervals on the surface of the electrode. A constant current is passed through the two outer probes, and the two inner probes measure the potential difference. The resistivity of the electrode is obtained according to Ohm's law, and then the resistance is calculated.
[0167] (c) Battery capacity test: The battery assembled above was tested for capacity at a voltage of 2-4V using a Blue Power battery testing system.
[0168] Figure 2 The first week charge and discharge curve of the sodium ion battery provided in Example 1 is shown. Figure 2 It can be seen that the material discharge curve is smooth, without complex phase change, and the material specific capacity is relatively high.
[0169] The test results of the above tests are shown in Table 3.
[0170] Table 3
[0171]
[0172] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polyanion sodium ion battery positive electrode material, characterized in that: The polyanion sodium ion battery positive electrode material comprises a polyanion positive electrode matrix material and a carbon coating layer coated on the surface of the polyanion positive electrode matrix material; The polyanion positive electrode matrix material is also doped with sodium and transition metal; The carbon source of the carbon coating layer includes an inorganic carbon source, and the specific surface area of the inorganic carbon source is 150-300m 2 / g.
2. The polyanion sodium ion battery positive electrode material according to claim 1, characterized in that The chemical formula of the polyanion positive electrode matrix material is Na x L y Fe a M b (PO4)2P2O7, wherein 3.5≤x+y≤4, 0<y<0.1, 1.32<(x+y) / (a+b)<1.38, b>0, L is a sodium doping element, and M is a transition metal doping element; The Na x L y Fe a M b In (PO4)2P2O7, 0<b≤0.05; the weighted radius of the atom of the M element is 49~95pm.
3. The polyanion sodium ion battery positive electrode material according to claim 1, characterized in that: The ash content of the inorganic carbon source is less than 3%; The powder conductivity of the inorganic carbon source is >1×10 4 S / cm.
4. The polyanion sodium ion battery positive electrode material according to claim 1, characterized in that: The specific surface area of the polyanion sodium ion battery positive electrode material is 8 to 20 m 2 / g; The polyanion sodium ion battery positive electrode material has micropores, and the volume ratio of the micropores is 30% to 50%; After the polyanion sodium ion battery positive electrode material is compacted by 3t pressure, its compaction density is 1.8-2.2g / cm 3 The electronic conductivity of the compacted powder is 3×10 -6 ~6×10 -6 S / cm; The phase purity of the polyanion sodium ion battery positive electrode material is greater than 90%.
5. A method for preparing a polyanion sodium ion battery positive electrode material as claimed in any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: Mixing a sodium source, a sodium doping source, a transition metal source, a transition metal doping source, an inorganic carbon source and a solvent to obtain a mixed solution, and spray-drying the mixed solution to obtain a precursor material; Sintering the precursor material to obtain the polyanion sodium ion battery positive electrode material; The specific surface area of the inorganic carbon source is 150-300 m 2 / g.
6. The preparation method according to claim 5, characterized in that: Based on the total mass of the non-solvent components in the mixed solution being 100%, the amount of the inorganic carbon source added is 2% to 6%; The particle size of the sodium doping source is D50<200nm, D100<10μm; The particle size of the sodium doping source satisfies: 1.0<(D90-D10) / D50<3.0; The band gap width of the sodium doping source is 1-10 eV.
7. The preparation method according to claim 5 or 6, characterized in that: The particle size of the transition metal doping source is D50<200nm, D100<10μm; The particle size of the transition metal doping source satisfies: 1.0<(D90-D10) / D50<3.0; The band gap width of the transition metal doping source is 1-10 eV.
8. The preparation method according to claim 5, characterized in that: The heating rate of the sintering is 1-5°C / min, the holding temperature of the sintering is 450-600°C, and the holding time of the sintering is 8-16h.
9. A positive electrode sheet, characterized in that: The positive electrode plate includes a positive electrode collector and a positive electrode active material layer located on at least one side of the positive electrode collector; the positive electrode active material layer includes a binder and the polyanion sodium ion battery positive electrode material according to any one of claims 1 to 5 or the polyanion sodium ion battery positive electrode material prepared by the preparation method according to any one of claims 6 to 8.
10. A sodium ion battery, characterized in that: The sodium ion battery comprises the polyanion sodium ion battery positive electrode material as described in any one of claims 1 to 5, or the polyanion sodium ion battery positive electrode material prepared by the preparation method as described in any one of claims 6 to 8, or the positive electrode sheet as described in claim 9.
Citation Information
Patent Citations
Positive electrode material, positive plate and sodium ion battery
CN117080393A
Sodium-iron double-doped polyanion positive electrode material and preparation method thereof
CN117558905A
K-doped polyanion positive electrode material and preparation method thereof
CN117810431A
High-energy density type polyanion positive electrode material, preparation method thereof and sodium ion battery positive electrode plate
CN117936755A
Positive electrode active material for sodium ion battery, sodium ion battery, and electric device
CN118299565A